2019
DOI: 10.1080/21691401.2019.1608218
|View full text |Cite
|
Sign up to set email alerts
|

Co-SLD suppressed the growth of oral squamous cell carcinoma via disrupting mitochondrial function

Abstract: To evaluate the safety and efficacy of novel cobalt complex with sulindac (Co-SLD), the zebrafish and oral squamous cell carcinoma CAL27 were investigated in the present study. The developmental toxicity of Co-SLD ranging from 5 to 20 lM was determined by exposure to 3-144-h post-fertilization (hpf) zebrafish. Our data showed that Co-SLD did not cause to the appreciable toxicity at low concentration (5 and 10 lM). A remarkable toxicity was observed at high concentration (20 lM), including increased mortality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(81 reference statements)
1
1
0
Order By: Relevance
“…Moreover, the frequency of tail contraction in 20 μM Co‐NMS‐exposed group was prominently reduced by 71.4% than that of in the control group (Figure 3b). These data suggested that the higher doses of Co‐NMS dramatically led to the behavioral abnormality at the earliest stages, which were in line with our previous outcomes (S. Li et al, 2019).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the frequency of tail contraction in 20 μM Co‐NMS‐exposed group was prominently reduced by 71.4% than that of in the control group (Figure 3b). These data suggested that the higher doses of Co‐NMS dramatically led to the behavioral abnormality at the earliest stages, which were in line with our previous outcomes (S. Li et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…The zebrafish (AB strain) were kept in our standard laboratory procedures (S. Li et al, 2019). Human U251 glioma cells were purchased from the BeNa Culture Collection (Beijing, China), and grown in Dulbecco's modified Eagle's medium containing 10% fetal bovine serum (Hyclone, Logan, UT) under 37°C of 5% CO 2 condition.…”
Section: Zebrafish Rearing and Maintenance And Cell Culturementioning
confidence: 99%